Evaluation of Clinico-Demographic Characteristics of Patients with Colorectal Carcinoma: A Multicenter, Observational Study - Awlad Hossain; ABM Saifullah; Chowdhury, Md Fazlul Karim; Susmita Islam; Abdullah Al Shah Newaz; Jubaere, A K M; Rahman, Md Atikur; Krishna Pada Saha; Miah, Md Shah Alam; Amin, Md Al; et al. (Bangladesh Medical Journal, 2026)
Colorectal carcinoma (CRC) remains a major contributor to global cancer morbidity and mortality, with incidence rising rapidly in developing nations due to dietary and lifestyle transitions. In Bangladesh, limited epidemiological surveillance and the absence of structured screening programmes lead to delayed diagnosis and poorer outcomes. is study sought to characterize the clinico-demographic, behavioural, and histopathological features of CRC to support early detection and prevention strategies. A hospital-based cross-sectional study was undertaken from January to December 2023 at two tertiary centres in Dhaka: Sheikh Russel National Gastroliver Institute and Hospital (SRNGIH) and the National Institute of Cancer Research and Hospital (NICRH). A total of 252 histologically con€rmed CRC patients were consecutively enrolled. Primary variables included age, sex, socioeconomic status, presenting symptoms, tumour location, histologic type, grade, and stage. CRC was more common in males (59.5%), with a mean age of 44.4 ± 13.3 years, and predominated among middle-income patients (90.5%). e rectum was the most common tumour site (46.8%), followed by the ascending colon (18.3%) and sigmoid colon (11.1%), with an overall left-sided predominance (61.9%). Major symptoms included unexplained weight loss (97.2%), loss of appetite (93.3%), per-rectal bleeding (78.6%), constipation (77.8%), and tenesmus (73.4%). Adenocarcinoma constituted 96.4% of cases, with most tumours moderately di.erentiated (79.8%) and diagnosed at Stage II (65.5%) or Stage III (22.6%). Modi€able risk factors were widespread: low daily fruit intake (15.9%), low vegetable intake (38.1%), high red-meat consumption (75.4% occasional or more), and low dairy intake (96.4% occasional). Common comorbidities included diabetes mellitus (31.0%) and hypertension (25.4%), whereas hereditary risk factors, including family history of CRC (3.17%) and familial adenomatous polyposis (0%), were uncommon. e €ndings indicate a strong association of CRC in Bangladesh with lifestyle-related and metabolic factors, consistent with trends observed in other rapidly transitioning middle-income countries. e predominance of Stage II and III disease underscores delayed symptom recognition and diagnostic access. Strengthening early evaluation of rectal bleeding and altered bowel habits in primary care and expanding multidisciplinary CRC services and cancer registries remain essential priorities. Bangladesh Med J. 2025 Sept; 54(1): 30-38